Perilaku asertif dan tipe kepribadian remaja yang mengalami kecenderungan neurotik - Rizki Maulana Hidayatullah; Finanin Nur Indana (PSYCOMEDIA : Jurnal Psikologi, 2022)
This study aims to examine the relationship between assertive behavior and personality type in adolescents with neurotic tendencies. The subjects of this research are teenagers who live in Surabaya as many as 351 students. The measuring instrument used in this study is the assertiveness scale, totaling 54 items, while measuring personality type using the introvert and extrovert personality scales totaling 65 items, and then measuring neurotic tendencies using the NSQ scale which amounts to 40 items. Data were analyzed using simple regression analysis. The results of the analysis show that The coefficient of determination obtained is 0.780, meaning that the ability of the independent variable to explain the variance of the dependent variable is 78%. Fcount obtained is 15.981. With a significance level of 5%, the F table obtained is f(α; k;n-k) or f(0.05;2;10) = 4.1. Where the value of n is the number of data and k is the number of independent variables. Because fcount > ftable = 4.1, then h0 is rejected, so it can be concluded that the score of assertive behavior and extrovert personality type significantly influence neurotic tendencies.